Application of rotary furnaces for melting ferrous alloys - S. L. Rovin; L. E. Rovin; I. S. Nasevich (Литьë и металлургия)
The article presents the experience of using rotary tilting furnaces (RTF) for melting ferrous alloys, as well as for recycling of dispersed iron-containing wastes (chips, dross, sludge) to obtain high – quality casting alloys directly in the RTF or when implementing the duplex process: RTF-induction furnace or RTF-arc furnace. The main technical characteristics of RTF that developed by Belarusian scientists and designers are described. The most promising areas of application of RTF were shown. An approximate calculation of the economic effect associated with the use of RTF in the production of steel and cast iron castings is performed.